2022
DOI: 10.3390/en15030847
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Analysis and Safety Assessment of Fresh and Electrical Aged Lithium-Ion Pouch Cells Focusing on Mechanical Behavior

Abstract: Analyzing the impact of electrical aging on the lithium-ion cell’s mechanical behavior and safety is an important factor to assess the crash safety of electric vehicles during their lifetime. In this study, fresh and electrical aged state-of-the-art NCM pouch cells were investigated. Aged cells, which were cycled electrically to 90% state of health, under laboratory conditions in electric vehicle battery modules were used. The used charging/discharging strategy represents real customer behavior based on accele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…In summary, it can be concluded that the effective impact force on a hypothetical impurity particle increases due to parallel ageing processes and with each charging cycle, as visualised in Figure 1. Moreover, the mechanical stability of the separator also decreases with cell ageing [58][59][60], as indicated by the red curve in Figure 1. For example, X. Zhang et al observed a reduction in strength by up to 30% after 1200 full cycles compared to the new condition in a punch test [59].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In summary, it can be concluded that the effective impact force on a hypothetical impurity particle increases due to parallel ageing processes and with each charging cycle, as visualised in Figure 1. Moreover, the mechanical stability of the separator also decreases with cell ageing [58][59][60], as indicated by the red curve in Figure 1. For example, X. Zhang et al observed a reduction in strength by up to 30% after 1200 full cycles compared to the new condition in a punch test [59].…”
Section: Introductionmentioning
confidence: 97%
“…For example, X. Zhang et al observed a reduction in strength by up to 30% after 1200 full cycles compared to the new condition in a punch test [59]. M. Sprenger et al also noticed a decrease by 25% in tensile strength, 50% in failure strain and 30% in Youngs modulus when investigating aged cells at an SOH of 90% [60].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, studies on battery safety assessment have been conducted in response to ISC and thermal runaway caused by mechanical abuse 36 39 . Based on mechanical abuse experiments, Ohneseit 40 and Ellersdorfer 41 conducted safety assessments by extracting characteristic parameters of battery failure for 18,650 batteries and pouch cells, respectively.…”
Section: Introductionmentioning
confidence: 99%